The Temperament Models of Sample of Heart Patients in Heart Surgery of Basel Center in Lattakia City “Afield Study” - Ali, Rania (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research try to defined the Temperament Models of sample of Heart Surgery of Basel Center in Lattakia City, as well as to identify in the differences between the mean responses of Heart Patients on a scale of Temperament Models to the variables (sex, place of residence, age). Use the search descriptive analytical method. Application a scale of Temperament Models on the sample included (142) male and female patients, for the year 2018,. Pilot sample consisted of (28) patients, Reliability was established by Cronbach – Alpha Reliability at least (0.958). Results showed that the field of the force in the excitement field was the most spreading between heart patients, and came after the dynamic operations of Neurotic field, at last the field of the power to cease operations. There are statistically significant differences according to six in favor of female, there are no statistically significant differences according to variables (place of residence, age) in the Temperament Models at sample of Heart Surgery of Basel Center in Lattakia City.